2008
DOI: 10.1111/j.1540-4560.2008.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Home Learning Environment and Preschool Center Experience upon Literacy and Numeracy Development in Early Primary School

Abstract: This study investigates the influence of aspects of home and preschool environments upon literacy and numeracy achievement at school entry and at the end of the 3rd year of school. Individuals with unexpected performance pathways (by forming demographically adjusted groups: overachieving, average, and underachieving) were identified in order to explore the effects of the home learning environment and preschool variables on child development. Multilevel models applied to hierarchical data allow the groups that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
427
4
30

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(478 citation statements)
references
References 41 publications
17
427
4
30
Order By: Relevance
“…Other studies have shown (45,46) that this can be done, for instance, by strengthening preschool education. However, Melhuish et al (47) indicated that even though such family factors as parents' education and SES are important, the quality and extent of home learning activities and home environment have a greater and independent influence on a child's academic achievement. Also, Belsky et al (48) showed that the quality of parenting preschool-aged children proved to be a stronger and more consistent predictor of children's developmental outcomes and school achievement when tested among 5th graders than did any of the other child-care predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown (45,46) that this can be done, for instance, by strengthening preschool education. However, Melhuish et al (47) indicated that even though such family factors as parents' education and SES are important, the quality and extent of home learning activities and home environment have a greater and independent influence on a child's academic achievement. Also, Belsky et al (48) showed that the quality of parenting preschool-aged children proved to be a stronger and more consistent predictor of children's developmental outcomes and school achievement when tested among 5th graders than did any of the other child-care predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Child poverty means lacking any of the resources necessary for child development which are social, cultural as well as material. It is obvious that a family's financial resources are important (including the education and employment of parents) but, as numerous studies have shown, so too is the home learning environment Risley 1995, 2003;Melhuish et al 2008;Melhuish 2010, 67;Cosgrove and Creaven 2013, 201;Curtin et al 2013, 6;Fernald, Marchman, and Weisleder 2013, 234;Williams et al 2013, 64-65) and the child's diet (Williams et al 2009(Williams et al , 63, 2013 and as well as the quality of interactions within the family. Poverty in this wider understanding gives rise to disparities in social and emotional skills and language and cognitive skills that were evident in this study when children started the Free Pre-School Year.…”
Section: Discussionmentioning
confidence: 99%
“…Resource factors include, for example, positive parenting characteristics such as higher levels of education and the amount of time and energy parents invest in their children (Lerner & Benson, 2003;Rutter, 1987Rutter, , 2006Masten, 2009;Schoon, 2006). For example, more involved parenting has been associated with better adjustment than expected among children exposed to socio-economic adversity (Bradley, Corwyn, McAdoo & Coll, 2001;Melhuish et al, 2008). In this paper we focus on the role of the early homelearning environment during the first three years of life on later academic performance, to assess its long-term benefit over and above a number of other control factors, such as variations in earlier cognitive performance and child behaviour adjustment.…”
Section: The Home-learning Environmentmentioning
confidence: 99%
“…Previous research has mostly focused on the long-term benefits of early pre-school education provision (George, Stokes, & Wilkinson, 2012;Sylva, Melhuish, Sammons, Siraj-Blatchford, & I. Taggart, 2010), although not all children, especially the most disadvantaged, are making use of this provision. A growing body of evidence suggests that the early home learning environment is one of the most important factors in explaining income-related gaps in cognitive development, especially during the early years (Dearden, Sibieta, & Sylva, 2011;Melhuish et al, 2008;Washbrook, 2010). Key indicators of early home-learning include parent's reading to the child, teaching behaviour and early skills, encouraging literacy activities, library visits, as well as establishing rules and regularity of routines, which form the basis of the home learning measures included in this paper (see also Bradley, Corwyn, McAdoo, & Coll, 2001;Kelly, Kelly, & Sacker, 2013).…”
Section: The Home-learning Environmentmentioning
confidence: 99%